Molecular Design, Synthesis, Computational Screening, Antimicrobial Evaluation and Molecular Docking Study of Acetylinic Isatin Hybrids. Issue 6 (13th February 2018) - Singh, Gurjaspreet; Arora, Aanchal; Singh, Akshpreet; Kalra, Pooja; Rani, Sunita; Singh, Kashmir; Maurya, Indresh K.; Mandal, Rahul S.
Abstract: As a part of our program to compose multicomponent hybrid templates with potential pharmaceutical recognition, we have designed a library of acetylinic isatin hydrazones (1 b‐1 p ) and acetylinic spiroisatins (1 q‐1 s ). All the synthesized motifs were thoroughly characterized and then evaluated for their antimicrobial activities followed by cytotoxic appraisal of the more potent compounds in Hek293 and HeLa human cancer cell lines. Computer aided drug design filtered the compounds considered unsuitable for screening purposes. Acetylinic isatin1 e was the most potent antibacterial scaffold with IC50 ≈ 1.95 μM against E. coli while1 n with bis‐isatin assembly was the lead compound against C. albicans with IC50 ≈ 15.67 μM. SAR allowed to have a thorough anticipation of the substituent effect on the observed bioactivities of the compounds. Further, docking studies of the selected scaffolds on admissible bacterial and fungal proteins elicited isatin1 a to exhibit highest ligand efficiency. Molecular interactions disclosed that 3'N substituted isatin derivatives may be considered ==as efficient candidates to curb bacterial and fungal diseases. Abstract : Schiff base allied acetylinic isatins and acetylinic spiroisatins were synthesized and well characterized followed by computational screening of the compounds. All the synthesized compounds were then evaluated for their antibacterial and antifungal activities. Compounds revealed excellent antibacterial potency. Compounds with good bioactivity were then undergone through docking evaluation to have a deeper insight into the molecular interactions of the docked ligands with the target proteins.